Changes in diabetes care indicators: findings from German National Health Interview and Examination Surveys 1997–1999 and 2008–2011. Issue 1 (19th November 2015) - Du, Yong; Heidemann, Christin; Schaffrath Rosario, Angelika; Buttery, Amanda; Paprott, Rebecca; Neuhauser, Hannelore; Riedel, Thea; Icks, Andrea; Scheidt-Nave, Christa
Abstract : Objectives: To investigate changes in type 2 diabetes care indicators over time in Germany. Methods: Adults aged 45–79 years with type 2 diabetes were identified from two national health examination surveys conducted in 1997–1999 (GNHIES98, n=333) and in 2008–2011 (DEGS1, n=526). We examined diabetes care indicators including treatment and preventive targets (glycemic control, blood pressure (BP), total cholesterol (TC), smoking, weight reduction, sports activity), self-management and care process measures (glucose self-monitoring, holding a diabetes passport, annual foot and eye examination; statin use), and the presence of diabetes-specific complications (diabetic nephropathy, retinopathy, neuropathy, diabetic foot, amputations) and comorbid cardiovascular disease (CVD) or chronic kidney disease (CKD). We calculated proportions of persons meeting these care indicators by survey and examined unadjusted and adjusted changes between surveys. Results: Significant improvement (GNHIES98 vs DEGS1) over time was observed for glycated hemoglobin (HbA1c) <7.0% (53 mmol/mol) (32.4% vs 65.4%), BP <130/80 mm Hg (32.0% vs 47.2%), TC <190 mg/dL (13.5% vs 41.9%), statin use (11.7% vs 35.9%), eye (51.1% vs 78.4%) and foot (48.0% vs 61.4%) examination within the past 12 months, diabetes-specific complications (29.7% vs 21.8%), and CVD (44.5% vs 37.1%). Blood glucose self-monitoring significantly increased (37.4% vs 62.8%), while holding a diabetes passport did not change. Current smoking did not change and obesity rose, although sports activity significantly increased over time. Proportions of adults achieving combination goals of HbA1c, BP, TC, and smoking cessation were low in both surveys in spite of significant improvement. Conclusions: In Germany, the quality of diabetes care improved over time. There is much room for improvement, in particular regarding preventive goals and diabetes self-management.